PERANAN BADAN USAHA MILIK DESA (BUMDES SEJAHTERA) DALAM MENINGKATKAN EKONOMI DESA CARIGADING KECAMATAN AWANGPONE KABUPATEN BONE - Andi Amitya Resty Dwiyanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2022)
Economic development can improve the standard of living of many people. The village government in this case is required to develop relevant policies to build a prosperous and civil society. One of the efforts made by the village government is the procurement of Village-Owned Enterprises (BUMDes) which are believed to be a forum for residents to improve themselves and also maximize the use of assets and resources owned by the village. Through BUMDes, economic improvement is carried out entirely by the village community. This study uses a qualitative descriptive method to explain more about the role of BUMDes in improving the village economy by using data collection techniques through interviews, observation, and documentation. The results show that BUMDes Sejahtera Carigading Village has a role in regulating the economy in the village, especially in the field of the rental business, simple social business, service business, microfinance business, community joint effort, in this case, the procurement of Pertamina and the rental of newlyweds. The success of BUMDes in Carigading Village is inseparable from obstacles so it is hoped that there will be an increase in financial assistance and the implementation of work programs can be thought out more carefully so that efforts to improve the village economy and village communities can be carried out optimally. Keywords: Role, Village-Owned Enterprises (BUMDes), Economy, Carigading Village